2018
DOI: 10.1042/cs20171273
|View full text |Cite
|
Sign up to set email alerts
|

Functional blocking of Ninjurin1 as a strategy for protecting endothelial cells in diabetes mellitus

Abstract: Ongoing efforts to remove pathological inflammatory stimuli are crucial for the protection of endothelial cells in diabetes. Nerve injury-induced protein 1 (Ninj1) is an adhesion molecule that not only contributes to inflammation but also regulates the apoptosis of endothelial cells. In the present study, Ninj1 was found highly expressed in endothelial cells in Type 2 diabetic mice and increased in high-glucose (HG) cultured HUVECs. Furthermore, we found that Ninj1 levels are up-regulated in endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 49 publications
2
27
0
Order By: Relevance
“…The proangiogenic effect found in our siRNA-mediated Ninj1 KD experiments indicates that endogenous Ninj1 has a negative effect on angiogenesis, which is in keeping with a previous report that angiogenesis was enhanced after functionally blocking Ninj1 using a neutralizing antibody or siRNA in diabetic mice 15 . In addition, increase in the function and survival of endothelial cells following treatment with a Ninj1 antibody was reported in a similar diabetic animal model 20 . In the present study, we found that endogenous Ninj1 KD enhanced angiogenesis and that in that situation, N-NAM exerted no angiogenic effect, which suggested that the proangiogenic effects of N-NAM resulted from the suppression of endogenous Ninj1.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The proangiogenic effect found in our siRNA-mediated Ninj1 KD experiments indicates that endogenous Ninj1 has a negative effect on angiogenesis, which is in keeping with a previous report that angiogenesis was enhanced after functionally blocking Ninj1 using a neutralizing antibody or siRNA in diabetic mice 15 . In addition, increase in the function and survival of endothelial cells following treatment with a Ninj1 antibody was reported in a similar diabetic animal model 20 . In the present study, we found that endogenous Ninj1 KD enhanced angiogenesis and that in that situation, N-NAM exerted no angiogenic effect, which suggested that the proangiogenic effects of N-NAM resulted from the suppression of endogenous Ninj1.…”
Section: Discussionmentioning
confidence: 65%
“…Given the importance of angiogenesis during recovery, N-NAM might be a useful starting point for the development of therapeutics that target neuro-recovery from postischemic damage. Attenuation of delayed inflammation by N-NAM may also contribute to promote functional recovery following cerebral ischemia since numerous reports, including ours, have demonstrated the anti-inflammatory effects of this peptide 17 20 , 22 . It is important to note here that since in the process of reparative angiogenesis, the interplay between the immune cells and growing blood vessels is important, pro-angiogenic effect is associated with anti-inflammatory effect if the postischemic brain.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Excessive ROS generation contributes to EC malfunction in diabetes (28). Previous studies have shown that ROS generation partly contributes to HG-triggered cell death of ECs (29,30). OS normalization, resulting from use of antioxidants, reduces damage to vessels in patients with diabetes (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that diabetes mellitus (DM), considered as a low-grade inflammatory disease, is one of the risk factors for endothelial dysfunction [43]. Furthermore, experimental and animal studies have demonstrated that Ninj1 expression was upregulated not only in ECs of type 2 diabetic mice and high-glucose (HG) cultured human umbilical vein ECs but also in ECs of clinical specimens for diabetics [44]. Moreover, in gain- and loss-of function experiments, Wang et al [44] elucidated that Ninj1 can facilitate the expression of proinflammatory genes, such as ICAM-1, VCAM-1, IL-6, and MCP-1, via modulating p38-MAPK and NF-κB pathways, and the formation of reactive oxygen species under HG condition.…”
Section: Roles Of Ninjurin1 Outside the Nervous Systemmentioning
confidence: 99%